Pengaruh Kumur Air dan Povidone Iodine Sirih 1% Terhadap Status Gingiva pada Pasien Setelah Tindakan Scalling - Sutrisno, Sutrisno; Almujadi, Almujadi (Poltekkes Kemenkes Yogyakarta, 2018)
In the scaling action will leave feeling pain, swollen gums, bright red color, sensitive and bleed easily. Usually the patient will be given an antiseptic that back healthy gums, such as povidone iodine 1%. Studies in the Faculty of Dentistry Indonesian some shows many medicinal plants native to Indonesia are efficacious for the teeth and mouth. Among them are betel efficacious anti-inflammatory antibacterial, antiseptic, and stop bleeding. This study aims to determine the effect of betel water gargle and mouthwash povidone iodine 1% of the gingival status in patients with post-scaling. To determine the effect of water gargle betel povidone iodine and 1% of the gingival status in patients with post-scaling. The research is a Quasi Experiment with One Group Pretest Posttest design. Samples taken were 30 people, divided into 2 groups of samples based on certain criteria (purposive sampling). Data analysis using t test. The result was no difference (segment unhealthy) before and after rinse your mouth with water betel and no difference (segment unhealthy) before and after rinse your mouth with povidone iodine 1%. No significant differences (segment unhealthy) after rinse your mouth with water after the betel or rinse your mouth with povidone iodine 1%.